Differential diagnosis of a calcified cyst found in an 18th century female burial site at St. Nicholas Church cemetery (Libkovice, Czechia) - Kwiatkowska, Barbara; Bisiecka, Agata; Pawelec, Łukasz; Witek, Agnieszka; Witan, Joanna; Nowakowski, Dariusz; Konczewski, Paweł; Biel, Radosław; Król, Katarzyna; Martewicz, Katarzyna; Lissek, Petr; Vařeka, Pavel; et al. (PloS one, 2021)
During archaeological excavations in burial sites, sometimes stoned organic objects are found, in addition to human remains. Those objects might be of a different origin, depending on various factors influencing members of a community (i.e. diseases, trauma), which provides information about their living conditions. The St. Nicholas Church archaeological site (Libkovice, Czechia) in the 18th century horizon of the cemetery, yielded a maturus-senilis female skeleton with a stone object in the left iliac fossa. This object was an oviform cyst-like rough structure, measuring 54 mm in length, 35 mm in maximum diameter and 0.2-0.7 mm shell thickness. Within the object there were small fetal bones (long bones, i.e. femur and two tibias, two scapulas, three ribs, vertebrae and other tiny bone fragments). Methods utilized to analyze the outer and inner surface morphology of the cyst and its inside, included: X-ray, CT imaging, SEM, histological staining and EDS. The EDS analysis revealed the presence of primarily oxygen, calcium and phosphorus in bone samples, and oxygen and silicon, in stone shell. Based on the length of the femur (20.2 mm) and tibia (16 mm) shafts, the fetal age was determined as being in the 15-18 week of pregnancy. The differential diagnosis was conducted, including for the three most probable cases: fetiform teratoma (FT), fetus-in-fetu (FIF) and lithopedion. The possibility of fetiform teratoma was discounted due to the presence of an anatomically correct spine, long bones and the proportions of the find. Although the low calcium content in the shell (2.3% atom mass), the lack of skull bones and the better developed lower limbs indicate fetus-in-fetu rather than lithopedion, the analyses results are unable to conclusively identify the object under one of these two categories since there are insufficient such cases in excavation material with which to draw comparison.
Keywords: Female; lidé středního věku; Calcium; Burial; Cemeteries; Fetus; plod; Humans; cysty; Czech Republic; lidé; Middle Aged; hřbitovy; Diagnosis, Differential; kosti a kostní tkáň; diferenciální diagnóza; ženské pohlaví; vápník; Česká republika; pohřeb; Cysts; Bone and Bones